Walking activity patterns in youth with cerebral palsy and youth developing typically. (July 2014) - Bjornson, Kristie F.; Zhou, Chuan; Stevenson, Richard; Christakis, Dimitri; Song, Kit
Abstract Purpose: To describe daily walking stride rate patterns of young children with cerebral palsy (CP) as compared to a typically developing youth (TDY) cohort relative to age and functional level. Method: A cross-sectional comparison cohort study compared 209 youth with CP with 368 TDY aged 2–13 years. Youth with CP had Gross Motor Function Classification System (GMFCS) levels I–III with 60% bilateral involvement and 79% spastic. Five days of StepWatch data were averaged and classified into low, moderate and high stride rates. Group differences were examined by t-test and analysis of variance. Results: Children with CP walk significantly less each day than TDY (F = 245, p ≤ 0.001) and differ by GMFCS (F = 1.51, p < 0.001). TDY walk a similar number of strides in low and moderate stride rates each day while youth with CP do not. TDY attained high stride rates (>60 strides/min) for 8 min/d with levels I–III at 4.0, 3.2 and 0.53 min/d, respectively. Conclusions: The relative relationship of walking intensity levels within total daily stride activity differs for youth with CP as compared to TDY. The influence of functional walking ability on walking stride activity levels and intensity does not appear to differ significantly across age groups. Implications for Rehabilitation Limitation in the ability to attain moderate stride-rate intensity, regardless of total number of strides taken each day for ambulatory youth with CP, is a potential area of focus for intervention. Understanding of stride activity levels and intensity in youth with CP may be employed to focus rehabilitation strategies to enhance habitual walking activity. Community-based stride rate data has potential as an effectiveness outcome for rehabilitation strategies focused on walking (i.e. orthopedic surgery, orthoses and injections therapies).